ENCUENTROS: Decolonizing the Academy and Mobilizing for Justice. (March 2023) - Ayala, Jennifer; Fine, Michelle; Mendez, Maria del Cielo; Mendoza, Andrea Nikté Juarez; Rivera, Juan Carlos Garcia; Finesurrey, Samuel; Villeda, Ariadna; Thelusca, Hermanica; Mena, Viandry; Azzam, Karim; Galletta, Anne; Houston, Angelica; et al.
In this article, we try to capture a moment when we were relatively steady in our belief that as persons working in/through the academy, we are accountable to the temblores, to take up the project of decolonizing the curriculum, democratizing our pedagogy, and sharing the very space we occupy with those most affected by current assaults on immigrants and people of color in the United States. We still believe this, perhaps even more from our homes of quarantine. Our universities are obligated to build ligaments of solidarity—material, intellectual, political, ethical—and spaces of sanctuary.